UHPLC-MS/MS profiling of histidine and bile acid metabolism in human gastric fluid for diagnosis of gastric diseases - Lee, Wonwoong; Um, Jinhee; Ko, Keon-hee; Lee, Yong Chan; Chung, Bong Chul; Hong, Jongki (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
Bile acids (BAs) are synthesized in the liver and can mediate homeostasis and various metabolism processes in the human body. Their levels in the gastrointestinal tract are closely related to various gastrointestinal diseases. In particular, farnesoid X receptor activated by free BAs is associated with overexpression of histidine decarboxylase in tumorigenesis. Therefore, comprehensive profiling of histamine (HIST), histidine (His), and BAs in biological samples can provide insight into the pathological mechanisms of gastrointestinal diseases. However, development of an analytical platform to profile HIST, His, and BAs in biological samples has several challenges such as highly different polarities between acidic and basic targets, low physiological concentrations of analytes, and high matrix interference of biological samples. In this study, an ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method combined with serial derivatization was developed to simultaneously determine HIST, His, and 5 BAs (cholic acid, deoxycholic acid, chenodeoxycholic acid, ursodeoxycholic acid, and lithocholic acid) in human gastric fluid. In serial derivatization, benzoyl chloride (BzCl) and N,N-dimethylethylenediamine (DMED) were used to selectively derivatize amino and carboxyl groups of analytes, respectively. After serial derivatization, all target derivatives were determined using a reverse-phase C18 LC column and positive multiple reaction monitoring (MRM) mode, with reasonable chromatographic separation and sensitive MS detection. To accurately quantify target metabolites, 7 stable isotope-labeled internal standards were used. The MS/MS spectra of DMED and Bz derivatives exhibited specific fragments via loss of a neutral molecule (dimethylamine; 45 Da) and inductive cleavage (benzoyl; m/z 105) from protonated molecules, enabling selection of appropriate MRM transition ions for selective and sensitive detection. The developed method was validated with respect to limits of detection and quantification, linearity, precision, accuracy, stability, and matrix effect. The established method was successfully applied to human gastric fluid samples. This method provides reliable quantification of HIST, His, and BAs in human gastric fluid and will be helpful to understand pathophysiological mechanisms of gastric diseases.
Keywords: BENZOYL CHLORIDE DERIVATIZATION; MASS-SPECTROMETRY; HELICOBACTER-PYLORI; POTENTIAL BIOMARKERS; HISTAMINE; JUICE; REFLUX; NEUROCHEMICALS; URINE; SERUM